Spreading pathways of Pilgrim Nuclear Power Station wastewater in and around Cape Cod Bay: Estimates from ocean drifter observations. (December 2022) - Rypina, Irina I.; Macdonald, Alison; Yoshida, Sachiko; Manning, James P.; Gregory, Margaret; Rozen, Nimrod; Buesseler, Ken
Abstract: Near-surface drifter observations were used to study the spreading pathways in and around the Cape Cod Bay from a source region located just offshore of the Pilgrim Nuclear Power Station. The study was motivated by the recent closing of the power plant and a possible release of accumulated wastewater. The investigation applies several different techniques to the drifter data set to estimate and quantify various aspects of the circulation and spreading. Our goal was two-fold: first, to better understand and predict the fate of the Pilgrim wastewater should it be released; and second, to review, compare, and contrast several useful techniques that can be applied to drifter datasets in other parts of the global ocean. Our analysis suggests weaker spreading of the wastewater plume inside the Bay than outside, and sensitivity of the advection pathways to the location of the release. Statistical techniques predicted that part of the plume would likely be advected cyclonically around the inner coastline of the Bay towards the more quiescent eastern regions, while another part of the plume would likely pass close to the tip of Cape Cod and the beaches of the Outer Cape. For the soluble radionuclides, the levels observed in our statistical model offshore of Provincetown and Dennis/Brewster will be at least 100 times smaller than the initial concentrations. Highlights: Study is motivated by potential contaminated wastewater release into Cape Cod Bay. Six methods were applied to drifter data to study transport pathways and spreading. Contamination release into Cape Cod Bay may affect both interior and outer Cape. Spreading is weaker inside Cape Cod Bay than outside.